2016
DOI: 10.1016/j.acvd.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

One-year incidence and clinical impact of bleeding events in patients treated with prasugrel or clopidogrel after ST-segment elevation myocardial infarction

Abstract: In this unselected STEMI population, the rate of major bleedings with prasugrel at 12months was low, but nuisance bleedings were frequent and led to more premature cessations than with clopidogrel. Prevention of bleeding complications, even minor, is necessary to prevent disruption of antithrombotic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Besides, the significant excess in non-CABG-related TIMI bleeding was not seen in STEMI patients undergoing PCI 43,44 . Contradictory findings in some observational studies reported the lower incidence of major bleeding with prasugrel 45,46 . Our network meta-analysis provided a more reliable conclusion by integrating direct and indirect evidence for analysis.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, the significant excess in non-CABG-related TIMI bleeding was not seen in STEMI patients undergoing PCI 43,44 . Contradictory findings in some observational studies reported the lower incidence of major bleeding with prasugrel 45,46 . Our network meta-analysis provided a more reliable conclusion by integrating direct and indirect evidence for analysis.…”
Section: Discussionmentioning
confidence: 88%
“…For example, previous studies concluded that there was no difference in bleeding incidence between prasugrel and clopidogrel [20, 21]. Other studies demonstrated that prasugrel, compared to clopidogrel, had more frequent minor/minimal bleeding events but fewer incidences of major bleeding events [22, 23]. The findings of the presented study determined that patients receiving prasugrel had a lower incidence of in-hospital major bleeding events compared to those administered clopidogrel, agreeing with the latter previous studies with long-term follow-up [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that prasugrel, compared to clopidogrel, had more frequent minor/minimal bleeding events but fewer incidences of major bleeding events [22, 23]. The findings of the presented study determined that patients receiving prasugrel had a lower incidence of in-hospital major bleeding events compared to those administered clopidogrel, agreeing with the latter previous studies with long-term follow-up [22, 23]. The lower incidence of major bleeding among the prasugrel group may be explained by selection bias such that prasugrel is prescribed to patients with a low risk of bleeding [22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…We identified potential predictors of bleeding by reviewing previously published risk scores for in-hospital and postdischarge bleeding events, [8][9][10][11][12][13][14][19][20][21] as well as studies that had reported on characteristics associated with bleeding after ACS. [22][23][24][25][26] Nineteen potential predictors were selected for inclusion in the study on the basis of clinical judgement.…”
Section: Predictorsmentioning
confidence: 99%